Animal Inflicted Maxillofacial Injuries: Treatment Modalities and Our Experience - Yadav, Anjani Kumar (J Maxillofac Oral Surg, 2016)
INTRODUCTION: Animal inflicted injuries to the face and neck are becoming much more common as people lavish affection on pets. Injuries caused by animal attacks to the face can cause complex injuries to soft and hard tissues, presented as perforations, lacerations, crushes, avulsion or fractures. An uncountable number of bacteria and virus can be found in such injuries, with a potential pathological effect to humans, regarding infections. Although the infection rate is low due to excellent blood supply to face, the injuries have disfiguring effect with possible psychological repercussion to the patients. The treatment of animal inflicted injuries must address the soft tissue defect, neurovascular injuries, and bone injuries as well as prevention of post treatment infection. Primary wound repair is the treatment of choice for most clinically uninfected bite wound where as delayed closure should be reserved for wounds at high risk of infection or already infected wounds and tissue defect may require local flap or micro-vascular re-implantations. MATERIAL AND METHODS: In this article, we have elicited up to date considerations regarding the management of animal inflicted injuries to the face based on literature search and exemplified by multiple case reports. CONCLUSION: For bite injuries on face, immediate primary wound repair after meticulous wound debridement and irrigation with sufficient volume added by antibiotic prophylaxis gives good cosmetic results with minimum risk of infection. Depending upon type of attack and age of victims, psychiatric or social counseling may also be required.